The effect of melatonin supplementation on the quality of sleep and weight status in postmenopausal women - Walecka-Kapica, Ewa; Klupińska, Grażyna; Chojnacki, Jan; Tomaszewska-Warda, Karolina; Błońska, Aleksandra; Chojnacki, Cezary (Menopause Review/Przegląd Menopauzalny, 2014)
Aim of the study : We evaluated the effect of melatonin supplementation on the nutritional status of postmenopausal women. Material and methods: The study included 56 women (51-65 years) and 25 healthy women (27-36 years). The emotional state was assessed using Hamilton Depression Rating Scale (HAM-D), the quality of sleep using Insomnia Severity Index (ISI). Body mass index (BMI) and waist-hip ratio (WHR) were also calculated. The patients were divided into 3 groups: group I (control) – 25 women with normal body weight, group II – 26 postmenopausal women with normal body weight, group III – 30 postmenopausal women with high body weight. In women from group II and III, routine laboratory tests, levels of thyroid-stimulating hormone (TSH), 17-estradiol, prolactin, follicle-stimulating hormone (FSH) and the concentration of 6-hydroxymelatonin sulphate (6-HMS) in day/night urine fractions were determined. On the day of the examination, women remained on a liquid diet (1800 kcal). Next, a balanced diet of 1500 kcal and 5 mg of melatonin administration were recommended. The follow-up examinations were performed after 4, 8, 12, 16, 20 and 24 weeks. Results : The patients from groups II and III showed similar mild levels of anxiety and depression and a significant degree of sleep disorders. In group III, lower urinary 6-HMS excretion was observed at night. In both groups a negative correlation was found between urinary 6-HMS excretion and the degree of sleep disorders. After 24 weeks, a statistically significant improvement of quality of sleep was obtained. A negative correlation was detected between urinary 6-HMS excretion and BMI. Conclusion : Melatonin supplementation contributed to body weight reduction.